The idea of justice - Sen, Amartya (Cambridge Belknap Press, 2009)
Social justice: an ideal, forever beyond our grasp; or one of many practical possibilities? More than a matter of intellectual discourse, the idea of justice plays a real role in how―and how well―people live. And in this book the distinguished scholar Amartya Sen offers a powerful critique of the theory of social justice that, in its grip on social and political thinking, has long left practical realities far behind.
Includes bibliographical references and indexes.
Keywords: Rawls, John, 1921-2002. Theory of justice